2013
DOI: 10.3109/14767058.2013.806891
|View full text |Cite
|
Sign up to set email alerts
|

New and old predictive factors for breech presentation: our experience in 14 433 singleton pregnancies and a literature review

Abstract: Objective. Breech presentation represents a common indication for primary cesarean section in women presenting for parturition. This study aims to investigate the presence of new and old risk factors for breech presentation and to provide a literature review.Methods. In this population-based retrospective cohort study we collected data from 14'433 consecutive singleton deliveries occurred in a 3rd level hospital setting of northeast Italy between January 2001 and July 2009. Related risk factors and trends in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
31
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 32 publications
(54 reference statements)
19
31
0
5
Order By: Relevance
“…Risk factors for breech presentation include older maternal age [5][6][7], nulliparity [5][6][7], preexisting diabetes [7,8], gestational diabetes [7], smoking [5], placenta previa [7], uterine abnormalities [6,9], previous breech presentation [10], previous caesarean section [5], small fetal size [5][6][7], and congenital anomalies [6,7,10]. There is also some evidence that the rate of breech presentation may differ by ethnicity, with women of African ancestry appearing to have the lowest rates [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for breech presentation include older maternal age [5][6][7], nulliparity [5][6][7], preexisting diabetes [7,8], gestational diabetes [7], smoking [5], placenta previa [7], uterine abnormalities [6,9], previous breech presentation [10], previous caesarean section [5], small fetal size [5][6][7], and congenital anomalies [6,7,10]. There is also some evidence that the rate of breech presentation may differ by ethnicity, with women of African ancestry appearing to have the lowest rates [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the "linear law" was not identified in early preterm births [13] or in pregnancies where the fetus presented severe malformations [5][6][7][8][9][10][11], two situations with a great rate of breech presentation (12% and 8%, respectively, Table 1). However, these two important pregnancy complications accounted for only 4% of the total population, the adjusted v 2 for linear trend remained very significant at a level of 64, while it was 68 for the entire cohort (p < 0.0001) ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Tompkins added to the list uterine anomalies, hereditary tendency, uterine scars, elderly primiparae and polyhydramnios. Later studies [5][6][7][8][9][10] discussed causes like oligohydramnios, polar placentation, gestational diabetes, short umbilical cord, a history of breech presentation, low birthweight and congenital anomalies. Cammu et al [10] in a recent study of 611,000 women in Flanders added also women giving birth to a female offspring to the list of risk factors, and, after controlling for confounding factors showed that gestational diabetes and pregnancies resulting from IVF were no more independent factors.…”
Section: Introductionmentioning
confidence: 99%
“…Breech presentation is associated with insufficient intrauterine space available for fetal movements, or other exogenous maternal and medical factors 7. Maternal constitutional factors include nulliparity, grand multiparity, contracted pelvis, high maternal age and uterine anomalies including fibroma.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal constitutional factors include nulliparity, grand multiparity, contracted pelvis, high maternal age and uterine anomalies including fibroma. Pregnancy complications associated with breech presentation include fetal malformations, fetal growth retardation, hydramnios, oligohydramnios, placenta previa and short umbilical cord 7 8. There are different types of breech presentation such as complete, frank, footling or kneeling breech.…”
Section: Introductionmentioning
confidence: 99%